A Single Route to Mammalian N‐Glycans Substituted with Core Fucose and Bisecting GlcNAc. Issue 44 (11th October 2018) - Luber, Thomas; Niemietz, Mathäus; Karagiannis, Theodoros; Mönnich, Manuel; Ott, Dimitri; Perkams, Lukas; Walcher, Janika; Berger, Lukas; Pischl, Matthias; Weishaupt, Markus; Eller, Steffen; Hoffman, Joanna; et al.
Abstract: The occurrence of α1, 6‐linked core fucose on the N‐glycans of mammalian glycoproteins is involved in tumor progression and reduces the bioactivity of antibodies in antibody‐dependent cell‐mediated cytotoxicity (ADCC). Since core‐fucosylated N‐glycans are difficult to isolate from natural sources, only chemical or enzymatic synthesis can provide the desired compounds for biological studies. A general drawback of chemical α‐fucosylation is that the chemical assembly of α1, 6‐linked fucosides is not stereospecific. A robust and general method for the α‐selective fucosylation of acceptors with primary hydroxy groups in α/β ratios exceeding 99:1 was developed. The high selectivities result from the interplay of an optimized protecting group pattern of the fucosyl donors in combination with the activation principle and the reaction conditions. Selective deprotection yielded versatile azides of all mammalian complex‐type core‐fucosylated N‐glycans with 2‐4 antennae and optional bisecting GlcNAc. Abstract : Core fucosylation on‐the‐fly : A highly α‐selective method was developed for the introduction of α1, 6‐linked core fucose into N‐glycans as the final step. A modular approach based on N‐TFAc protection for the antennae provides all the natural combinations of bisecting GlcNAc and core fucose found in mammalian complex‐type N‐glycans via a single pathway.